Experimental Investigation of dynamic stall control on a rotor airfoil using unsteady plasma actuation - Chang, W.; Zhiqiang, C.; Xin, Z.; Guoqiang, L.; Haowen, W. (My University, 2019)
Experimental study of the rotor airfoil’s dynamic stall control using plasma were carried out. The ability of unsteady plasma flow control was verified. It is found that only 20% duty cycle can achieve obvious control effects. Then the study of nondimensional frequency of the actuator was carried out. And the best control effect is observed when F+=1~2. Finally, according to experimental data analysis of the mechanism of plasma control, it is found that plasma excitation is mainly responsible after dynamic stall vortex’s shedding. Both steady excitation and unsteady excitation can significantly promote the recovery of the leading edge pressure gradient, and the effect of unsteady excitation is more effective.